Auditoría Financiera al Gobierno Autónomo Descentralizado Parroquial Honorato Vásquez del Cantón Cañar, periodo 2021 - Fajardo Guaman, Maryorie Vaneza (2023)
The Curricular Integration work called FINANCIAL AUDIT OF THE HONORATO VAZQUES PARISH DECENTRALIZED AUTONOMOUS GOVERNMENT, PERIOD 2021; was oriented to fulfill the objectives that refer to evaluating the internal control system according to the provisions of the laws, regulations, and norms in force for the Honorato Vásquez Parish GAD; determine the reasonableness of the accounts reflected in the financial statements, through the application of methods and procedures following the audit programs, and prepare the final financial audit report containing comments, conclusions, and recommendations in order to present a contribution to the administrators of the GAD for proper and timely decision making. To meet with the financial audit, a prior visit was made to the Honorato Vásquez Autonomous Decentralized Parochial Government to collect timely information that allows the entity to be known, and then internal control evaluations were carried out on each of the components in order to determine the level of risk, the audit approach, and the reasonableness of the balances presented in the financial statements, which were analyzed and verified, verifying compliance with current regulations and Generally Accepted Accounting Principles. Through the execution of the procedures established in the different audit programs, each of the working papers was analyzed, verified, and designed, based on international auditing standards that allowed determining the reasonableness of the balances presented in the financial statements, therefore, it is recommended to carry out an annual financial audit to demonstrate the reasonableness of the accounting balances, or in the same way, determine failures or errors in the administration and make pertinent corrective decisions.